Reduced Milk Production, Economic Losses, and Risk Factors Associated to Subclinical Hypocalcemia in Holstein Friesian × Zebu Crossbreed Cows in North-West Ethiopia - Mekonnen, Sefinew Alemu; Alelgn, Zegeye; Saudik, Seid; Molla, Wassie; Fentie, Tsegaw; Jemberu, Wudu Temesgen (Frontiers in Veterinary Science, 2022)
Hypocalcemia is a metabolic disorder that occurs when calcium leaves the blood to support milk production or for the growth of the fetus faster than calcium can be put back into the blood. Subclinical hypocalcemia (SCH) refers to clinically normal cows but with concentrations of calcium lower than measured in normal cows. A study was conducted to estimate economic losses and to identify risk factors associated with SCH in Holstein Friesian × Zebu crossbreed Cows in North-West Ethiopia. A total of 221 lactating dairy cows obtained from 81 dairy farms were selected and serum samples were collected and analyzed to estimate the level of calcium in the serum using an automated electrolyte analyzer (Roch, UVL Japan, 2014). Forty-seven cows obtained from 12 farms were grouped into two: cows with SCH and cows without SCH and milk yield was measured for eight consecutive days to estimate milk production loss associated with SCH. Prevalence was estimated and univariable and multivariable logistic regression analyses were used to identify determinants of SCH. The prevalence of SCH was 20.3% (51/221, 90% CI = 18.6%−28.1%). Grazing on pasture, membership to dairy cooperative, feeding above the cows' requirement (based on farmers' opinion), and previous experience of metritis reduced the odds of SCH (P < 0.05). The average economic losses associated with reduced milk production due to SCH were 11.25 Ethiopian Birr (ETB) (1 ETB = 0.023 US Dollar) and 3,026.25 ETB (69.6 US Dollar) per cow per lactation, respectively. The main findings of the study have shown that SCH was a problem in crossbreed dairy cows in Northwestern Ethiopia and identified few risk factors that could be targeted to mitigate the problem. Actually, in this study, the economic cost of SCH was significant and needs attention in the dairy extension and dairy health training programs.